2019
DOI: 10.1242/jcs.234492
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro compartmental system underlines the contribution of mitochondrial immobility to the ATP supply in the NMJ

Abstract: The neuromuscular junction (NMJ) is the largest, most complex synapse in the human body. Motor neuron (MN) diseases, such as amyotrophic lateral sclerosis (ALS), specifically target MNs and the NMJs. However, little is known about the reasons for MN selective neuronal and synaptic vulnerability in MN diseases. Here, utilizing a compartmental microfluidic in vitro co-culture system, we provide a possible explanation why the NMJ, other than its unusual dimensions, differs from other synapses. Using live imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…As we show, the NMJ relies on mitochondria activity (Fig. 5A-D) 31 and on local synthesis ( Fig. 5E-G).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…As we show, the NMJ relies on mitochondria activity (Fig. 5A-D) 31 and on local synthesis ( Fig. 5E-G).…”
Section: Discussionsupporting
confidence: 55%
“…3B vs. 3D). As NMJs are enriched with mitochondria 31,48,49 , and due to mitochondrial dependency on local synthesis 21,50 (Fig 4G-H), the enhanced local synthesis in NMJs can be attributed to its mitochondrial density. This suggests that the high polarization of MNs leads to higher dependency on local synthesis of mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, Altman et al (2019) showed that, compared with sympathetic neurons, cultured MNs displayed higher axonal and synaptic mitochondrial immobility. This finding suggests that the accumulation of mitochondria in the neuromuscular junction (NMJ) may play a significant role in MN function (Altman et al, 2019).…”
Section: Abnormal Mitochondrial Dynamics and Alsmentioning
confidence: 99%